Live sport monitoring using remote camera system - Sirichai, Apatcha; Kaviya, Somkuan; Yupapin, Preecha P. (My University, 2010)
We present the use of camera for sport judge, where the best sport broadcasting soccer which is popular worldwide to be more interesting with the right result. The audience which is known as sport fan club or spectators expects the right competition results, which may be concerned the gamblers. We use a remote camera system for the game clarification, i.e. fair play because the criticism of judges and the referees may be inappropriate behaviors. We use the system based on closed circuit television (CCTV) cameras to support judges and the lineman decision. Moreover, the monitoring of audience and game can be provided by using the registered and telescope cameras, respectively, which mean that the game result with fairly play can be seen over the audiences.
Keywords: Director of judges; Innovative communication; Live sport monitoring; Remote security cameras; Security